ON THE ISSUE OF THE GOAL OF POSTGRADUATE TRAINING (DISSERTATION VS QUALIFICATION) - Boris I. Bednyi (Высшее образование в России)
In the framework of the discourse on the third level of higher education, we examine some issues concerning the definition of the goals of a new type of postgraduate school and the expected results of postgraduate training. Based on the comparison of current approaches to the formulation and implementation of the goals of postgraduate studies, the author substantiates the conclusion concerning the prospects of the «competency-based approach » oriented towards the labor market. Within this approach, the preparation of the dissertation is an important task, but not the only one. The main objective is to prepare experts who know not only their «own » field, but also the related fields of science, who are capable of working in research teams, who are prepared to research work, teaching and innovation, who are able to plan and solve the tasks of their own professional and personal development. Possible criteria and the format of the graduates' final state certification are also discussed. It is shown that in the framework of the existing postgraduate school model, the difference between the presentation of a research report on the main results of the postgraduate student's qualifying research work and the defence of a Candidate of Sciences dissertation will remain essential in most cases.